Powder sample‐positioning system for neutron scattering allowing gas delivery in top‐loading cryofurnaces. Issue 2 (18th March 2016) - Lee, Stanley; Chevreau, Hubert; Booth, Norman; Duyker, Samuel G.; Ogilvie, Stephen H.; Imperia, Paolo; Peterson, Vanessa K.
Abstract : A system is presented for positioning powder samples in top‐loading cryofurnaces during neutron scattering experiments while delivering set quantities of gases at set temperatures to the sample. The positioning system separates into an upper and a lower section, and the lower section can be inserted into a glove box for loading and sealing of a sample without exposing it to air. Abstract : A system for positioning powder samples in top‐loading cryofurnaces during neutron scattering experiments, while facilitating the successive delivery of gas doses at set temperatures to the sample, has been designed and tested. The positioning system is compatible with a Hiden Isochema IMI instrument as a gas‐dosing platform, enabling gases to be delivered to the sample through a centrally located and thermally stabilized capillary line and valve. The positioning system separates into an upper and a lower section, with the lower section enabling the sample to be isolated and inserted into a glove box. This work describes the system using example neutron powder diffraction results obtained with this system in closed‐cycle cryofurnaces.